(untitled) (Balthazar, 2024)
In Kafka or about exactness I propose to read In der Strafkolonie as a description of the way in which Kafka’s texts work on the reader: elusive meanings, impossible to fully understand, are imprinted on his/her body and become, as the experience continues (if one enters in Kafka’s textual machine), a sort of scheme engraved on and/or under his/her skin, the background that guides the experience of things, of oneself, of the world. An operative habitus, a sort of transcendental structure – but corporeal, quasi-physical. Kafka’s word marks our corporeal ego thanks to its exactness: not the exactness of words and languages of sciences, naturally, but a different one, analogous, I don’t know if identical, to that of poetry.